Creating And Marketing An Ideal Investment Environment - J. Jegathesan, J. Jegathesan (Asian Academy of Management (AAM), 1996)
The focus of this paper is on attracting the "export-oriented investor". An investor has the free choice of various locations in any region, or even the world, for the establishment of his project. Many developing countries and in fact most developed countries are "bending backwards" to either attract or retain the manufacturer who has an export-oriented project. A local investor has little choice in respect of location and will be prepared to put up with all types of hardships, red-tapes, corruption etc., so as to make a living. Some foreign investors, seeking to set up import-substituting or resource-based projects, may also be prepared to tolerate difficulties and red-tape as long they have the assurance of a protected domestic market or easy access to raw materials. However, given the new opportunities springing up around the world and the limited amount of investment capital, even these types of foreign investors have a choice of several locations for import substituting industries. They will choose the location where the investment environment gives the least problems of a "non-business" nature.